2015
DOI: 10.1145/2717318
|View full text |Cite
|
Sign up to set email alerts
|

Ohmage

Abstract: Participatory sensing (PS) is a distributed data collection and analysis approach where individuals, acting alone or in groups, use their personal mobile devices to systematically explore interesting aspects of their lives and communities [Burke et al. 2006]. These mobile devices can be used to capture diverse spatiotemporal data through both intermittent self-report and continuous recording from on-board sensors and applications. Ohmage (http://ohmage.org) is a modular and extensible open-source, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…For the former, the deployment showed that the framework's campaign editor effectively enabled campaign authors to intuitively design their desired participatory sensing campaigns that collect meaningful city-related information on one hand, and that the framework's mobile application effectively assisted data collectors in gathering various types of data through their mobile devices on the other hand. This result reaffirms the potentials, applicabilities and effectiveness of multi-purpose participatory sensing frameworks, with Citizense as an example, in collecting a large variety of data in different scenarios [30,31].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…For the former, the deployment showed that the framework's campaign editor effectively enabled campaign authors to intuitively design their desired participatory sensing campaigns that collect meaningful city-related information on one hand, and that the framework's mobile application effectively assisted data collectors in gathering various types of data through their mobile devices on the other hand. This result reaffirms the potentials, applicabilities and effectiveness of multi-purpose participatory sensing frameworks, with Citizense as an example, in collecting a large variety of data in different scenarios [30,31].…”
Section: Discussionsupporting
confidence: 60%
“…Participatory sensing has been utilized in various application domains [13], such as bird conservation [25], urban infrastructure monitoring [26], traffic monitoring [27], radio signal strength measuring [28] and other information in the city [29]. The plethora of participatory sensing applications can be divided into two groups: single-purpose applications (i.e., [26,27]) and multi-purpose applications or frameworks [30,31]. The emergence of these multi-purpose participatory sensing applications shows a significant change in the realization of the participatory sensing concept.…”
Section: Volunteered Geographic Information and Participatory Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is exactly why more recently, several reconfigurable and reusable frameworks for mobile sensing applications have been proposed. Projects such as Sensr [8], Epicollect [3], ODK [2], and ohmage [12] provide frameworks for constructing mobile data-gathering tools. However, these configurable frameworks limit the type of data that can be collected (typically only through a form).…”
Section: Introductionmentioning
confidence: 99%